Free trade agreements and development: A global analysis with local data - John Cruzatti (University of Heidelberg, Department of Economics, 2021)
This paper analyzes the effects of Free Trade Agreements (FTAs) on various measures of local development in 207 countries over the 1990-2015 period. Using a Difference-in-Differences approach, I exploit spatial and time variation by comparing regions with (exogenously determined) exploitable and non-exploitable land before and after FTAs are "activated". I show that FTAs have a limited yet positive impact on a region's human development (as measured by the Human Development Index). The results also indicate that this limited impact can be explained by the positive effects of Free Trade Agreements on economic activity (night lights and GDP), together with the lack of significant in uence on patterns of inequality (distribution of night lights among population). Finally, I also show that FTAs' impacts on human development are stronger for urbanized regions. Conversely, there is neither clear evidence of a weaker positive effect if trade partners belong to the Global North nor if the agreements include arrangements beyond the elimination of tariffs and quotas.
urn:nbn:de:bsz:16-heidok-300398
Keywords: F13; F63; R12; 330; FTAs; Human Development; Economic Activity; Inequality